Dialogismo e interação discursiva : uma análise Bakhtiniana da mobilização de repertório sociocultural em redações do ENEM - (:unkn) unknown (Universidade Estadual de Goiás, 2023)
This research intends to discuss the mobilization of sociocultural repertoire in model essays elaborated by students that executed the Exame Nacional do Ensino Médio (ENEM), 2020 edition. The study starts from what is expected by competency 2 from the exam’s reference program, according to which the candidate, besides comprehending the essay’s proposal, should utilize knowledge from diversified areas, related to the proposed theme, in order to elaborate an argumentative and dissertation text. It is possible to affirm, according to bakhtinian concepts, that this process of texting production occurs by means of dialogical relations, inherent to the process of discursive interaction that materializes itself in essays evaluated by the correction board of the exam (ENEM). Among these essays, the ones with the highest scores, 1.000 points, are highlighted, and they become a template and paradigm to students and graduates from high school that also want to succeed in the exam. This investigation is anchored on the social and historical perspective, and approaches the mobilized speeches by the candidates' use of language, in means to effect their thought and occupy their place in the world. In this way, the analyzed essays are discussed, considering the social and historical position of the author-subject and the voices that constitute their speech. This study is a bibliographical and documentary research of qualitative character, and takes the Enem’s model essays as elements that reveal traces of a pedagogical culture about text labor in school. This study’s corpus is composed by ten essays evaluated with a thousand points in the 2020 edition of ENEM, analyzed based on concepts formulated by Bakhtin and other authors, that also start from the comprehension that language is an interaction process, marked by dialogism, as the text is a social product that materialize a speech, a way of seeing, of thinking and of acting in the world. In this way, the research reflects the dialogism materialized in text products of the 2020 ENEM’s candidates, in order to contribute to the debate about speech, about language and about textual production teaching. Among this study’s mains results, it emphasizes the perception that ENEM’s essay, as a process and production of dialogical relations given in a determined social, cultural and historical context, results from the mobilization of marked and unmarked social voices in the textual texture, revealing what the scholars of Bakhtin’s Circle named dialogism and heteroglossia.
Dialogism and discursive interaction : a Bakhtinian analysis of mobilization of sociocultural repertoire in ENEM writings
Keywords: Redação do Exame Nacional do Ensino Médio (Enem); Repertório sociocultural; Interação discursiva; Dialogismo; Heteroglossia; Exame Nacional do Ensino Médio (Enem) - Essay; Mobilization of social; Cultural repertoire; Discursive interaction; Dialogism; Heteroglossia; CIENCIAS HUMANAS::EDUCACAO